Maternal predictors of Low Birth Weight among women attending private hospitals of Lahore, Pakistan - Saeed, Ayesha; Saeed, Amina Muhammad (Progress in Nutrition, 2017)
Background: Low Birth Weight (LBW) is a global public health concern. In Pakistan, little progress has been made towards achieving the Millennium Development Goals. The study objective was to identify maternal predictors of LBW infants among women attending private hospitals in Lahore, Pakistan. Method & Materials: A descriptive cross-sectional study was conducted at three randomly selected tertiary care private hospitals in Lahore, Pakistan. A total of 225 participants were consecutively approached to participate in the study, 75 from each hospital. 164 gave written informed consent; the response rate was 73%. Data on demography was collected with the help of a piloted, structured questionnaire. Previous maternal anthropometric measurements, birth weight, mode of delivery, gestational age, sex and intra uterine growth retardation was obtained from patient’s file. Descriptive statistics, correlations, Anova and Chi-square was applied. A p-value of 0.05 was taken as statistically significant. Results: Inferential statistics revealed that maternal age of less than 24 years (F=4.531, p<α; X2=12.170, p<α); height less than 150cm (F=2.884, p<α; X2=8.187, p<α); booking weight less than 61 kg (F=4.080, p<α; X2=11.138, p<α); weight 27-32 weeks less than 63 kg (F=3.646, p<α; X2=10.086, p<α) was significantly associated with low birth weight in newborns. No association was found between BMI 1, BMI 2, education, parity and income. Conclusion: We concluded that birth weight of a newborn reflects maternal health and nutritional status; and maternal age, height and weight are predictors of low birth weight among women attending private hospitals. Mothers should be counseled regarding importance of adequate pre-pregnancy weight and weight gain during pregnancy.